PENGARUH FAKTOR SOSIAL DAN LINGKUNGAN TERHADAP PERKEMBANGAN BAHASA ANAK USIA 2-5 TAHUN - Kartikasari, Ratna Dewi; Zaharani, Rahma (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Human lives in a societal environment that influences growth and development, both physically and non-physically, from the prenatal stage to the end of life. Children's language development serves as a crucial indicator reflecting the interplay between biological, cognitive, and social aspects. This study aims to analyze children's language development using a qualitative method with a case study approach. Interviews were conducted with three children using five questions covering self-perception, education, environmental cleanliness, parental roles, and social interactions. The results reveal that the first child exhibits simpler and more descriptive language development, while the second child demonstrates a more reflective thought process. Environmental factors, parenting styles, and social experiences emerge as key determinants of language development. Children aged 2 years tend not to think about serious matters regarding environmental factors, while children aged 3 years are more exposed to physical activity and pragmatism, and finally children aged 5 years have a deep understanding of environmental issues and independence. These findings emphasize the importance of democratic parenting styles and environmental stimulation to support optimal language development in children.